PUTUS PERKAWINAN KARENA LI’AN DAN AKIBAT HUKUMNYA TERHADAP HARTA PERSPEKTIF HUKUM ISLAM DI INDONESIA - Harmi Yusri; Jumni Nelli (Khulasah : Islamic Studies Journal, 2025)
Marriage is a sacred bond aimed at forming a harmonious, loving, and compassionate family. However, in practice, various domestic issues may lead to divorce, one of which is through the li’an process. Li’an occurs when a husband accuses his wife of adultery without presenting four witnesses, and the wife denies the accusation by taking an oath before a judge. This process results in the permanent dissolution of the marriage and carries legal consequences, including the status of children and the division of marital property. This study employs a library research method by examining Islamic legal literature and relevant Indonesian regulations. The findings indicate that although Islamic law does not explicitly regulate the division of assets after li’an, resolution can be pursued through as-shulhu (amicable settlement) based on mutual agreement between both parties. If no agreement is reached, the matter may be resolved through the court while still adhering to the principles of Sharia.